ANALISIS SISTEM PROTEKSI PRIMARY AIR FAN PADA UNIT 1 DI PLTU PAITON - Dzakky kaffa Maharani; iham arifin pahlawan (ENIGMA: Engineering in Green Machinery, 2026)
Electricity is a very important energy to meet human needs in various fields. Steam Power Plants (PLTU) play a crucial role in producing electrical energy, by converting chemical energy from coal into electrical energy. This conversion stage goes through three stages: conversion of chemical energy into heat energy, heat energy into mechanical energy, and finally into electrical energy. This research focuses on PT. PLN NUSANTARA UP PAITON, one of the largest PLTUs in Indonesia, located in Probolinggo with a total capacity of 2 x 400 MW. The research method used is utilizing literature studies as a source of information, data collection techniques through observation and interviews with related parties. The results of the study show that the Primary Air Fan (PA Fan) has an important role in the combustion process in the boiler, including drying coal powder and regulating air flow to the pulverizer. In its working process, the primary air fan has a protection system to protect the PAF when a disturbance occurs, there are nine protections owned by the primary air fan. In addition, a protection system encompassing various instruments, such as thermocouple sensors and vibration sensors, is implemented to ensure the safety and operational efficiency of the PAF. These include thermocouple sensors, RTD sensors, and vibration sensors.